The Use of the Dictogloss Technique to Improve Students Listening Ability in the Era of COVID-19 at the University of Muhammadiyah Bone - Dian Riani Said; Gunawan Gunawan; Abdul Rahman (Acitya: Journal of Teaching and Education, 2023)
The objective of the research was to find out whether or not the use of Dictogloss technique can improve students’ listening ability. Besides, it was to find out the activeness learning of short conversation or narrative text is implemented in listening ability. The method of this research was Classroom Action Research by using Kurt Lewin’s model. The researcher used 2 cycles. Subject of the research in the third semester English Department of Muhammadiyah University of Bone. The instruments of the research were observing, questionnaire, and English test which was divided into three parts, they were diagnostis test, cycle test 1 and cycle test 2. This research revealed that there were 37,95% improvements of the student’ mean score from D-test to cycle test 1 in the first cycle and 61,22% improvements of the students’ mean score from the cycle test 1 in first cycle to the cycle test 2 in the second cycle. The observation result showed that the method could also increase the student team work through discussion in group, add their new vocabularies, increase their pronunciation and student’ involvement, it could be concluded that Dictogloss technique could improve the students ability in listening at the third semester English Department students of Muhammadiyah University of Bone and this Classroom Action Research was success because it had gained the target.